A new species of Metreletus Demoulin, 1951 from the far eastern region of Russia (Ephemeroptera: Ameletidae) - Tiunova, Tatiana M. (Zootaxa, 2012)
Metreletus omelkoi sp. nov. (male, female imagines and male, female subimagines, larvae and egg) is described from the fareastern region of Russia. The genus Metreletus Demoulin, 1951 has a trans-Palaearctic distribution and includes two species:the West-European mountain species, M. balcanicus Ulmer, 1920, and the Far-Eastern species, M. micus Bajkova, 1976. Metre-letus omelkoi sp. nov. is the second species from Far-Eastern Russia and the third globally. The larvae of M. omelkoi sp. nov.differ from the other species in their genus by the size of gill I (M. micus) and the form of gills II–VII (M. balcanicus). The male imago of the new species can be distinguished from M. balcanicus by shape, the penis lobes.